2015
DOI: 10.5194/isprsarchives-xl-7-w3-277-2015
|View full text |Cite
|
Sign up to set email alerts
|

Prospect inversion for indirect estimation of leaf dry matter content and specific leaf area

Abstract: ABSTRACT:Quantification of vegetation properties plays an indispensable role in assessments of ecosystem function with leaf dry mater content (LDMC) and specific leaf area (SLA) being two important vegetation properties. Methods for fast, reliable and accurate measurement of LDMC and SLA are still lacking. In this study, the inversion of the PROSPECT radiative transfer model was used to estimate these two leaf parameters. Inversion of PROSPECT traditionally aims at quantifying its direct input parameters rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…campaigns assisted for reasonable parameterisation of the model. The obtained result is in line with earlier findings by Yuan et al (2015) and Ali et al (2015) who demonstrated the effect of stand characteristics on INFORM simulated canopy reflectance. In general, a close match was observed between the measured and simulated reflectance spectra of RapidEye and Sentinel-2 in the visible, and the red-edge region where the average absolute errors (AAE) were below 0.02 for both sensors (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…campaigns assisted for reasonable parameterisation of the model. The obtained result is in line with earlier findings by Yuan et al (2015) and Ali et al (2015) who demonstrated the effect of stand characteristics on INFORM simulated canopy reflectance. In general, a close match was observed between the measured and simulated reflectance spectra of RapidEye and Sentinel-2 in the visible, and the red-edge region where the average absolute errors (AAE) were below 0.02 for both sensors (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…At last, we calculated the leaf dry matter dividing the dry weight (mg) of a leaf by its water-saturated fresh weight (g) (Ali et al 2015).…”
Section: Collection Of Functional Characteristicsmentioning
confidence: 99%
“…The ProSAIL model is widely used in agricultural (Ali et al, 2015;Richter et al, 2009;Vuolo et al, 2010) and ecological studies (Feilhauer et al, 2018;Punalekar et al, 2018). Although considerable high accuracies in parameter retrieval are found in literature, ProSAIL is a relatively simple 2-D model.…”
Section: The Prosail Radiative Transfer Modelmentioning
confidence: 99%